Estimated VO2 max Analysis with Six-Minute Walking Test on Obese Patients in Primary Health Care in Makassar - Kastiran, Andi Muhammad Akram; Amir, Muzakkir; Mappangara, Idar; Djafar, Zaenab; Warliani, Melda; Zainuddin , Andi Alfian (Nusantara Medical Science Journal, 2023)
Introduction: Obesity poses a severe threat to global health, making it a significant epidemiological concern that requires special attention. It is associated with several risk factors for various diseases. Alarmingly, one in three Indonesian adults is obese, with the obesity rate steadily increasing. Studies have shown that excess fat mass is linked to higher mortality and morbidity from cardiovascular disease, which is currently Indonesia's leading cause of death. To assess a person's functional capacity and ability for basic physical activity, the 6-minute walking test (6MWT) is utilized, as it proves to be a powerful predictor of morbidity and mortality rates. Therefore, this study aims to analyze the association between VO2 max using 6MWT in obese patients of Makassar City. Methods: This study was a cross-sectional study. The samples comprised all obese individuals who provided signed approval letters and were registered at Makassar City's 20 Public Health Centers. Consecutive sampling was used to gather the samples. Subsequently, the samples were examined and categorized based on their level of obesity.   The 6MWT results are then used with Nury's Formula to produce an estimated VO2max result. To analyze the association between VO2 max using 6MWT and obesity, statistical analysis was conducted using the Mann-Whitney test, with significant results indicated by (p < 0.05). Results: A total of 163 participants comprised the study's sample, with the majority being female and aged 50 years or older. After filling out the questionnaire, data show that most of the obese participants had a family history of cardiovascular disease (CVD), experienced significant stress levels, and had average BMIs falling into the category of obesity. According to the study, the average distance covered in the 6-minute walking test was 340.18 meters (±82.6 meters). When the study participants were ranked by their estimated VO2 max, the average value was 15.10±5.52 for those with first-degree obesity. Following them were participants with second-degree obesity, with results averaging 15.03±5.39 (p = 0.021). Conclusion: A significant inverse association exists between obesity and VO2 max, which means that the more obese a person is, the lower their VO2 max tends to be.